Nutrisi untuk Stunting - Julius Anzar (Fakultas Kedokteran Universitas Sriwijaya, 2019)
Stunting / stunted growth / nutritional stunting is a decrease in height growth rate as measured by the value of height by age under minus 2 standard deviations of the WHO child growth standards graph. In 2016 as many as 22.9% (154.8 million) of children under 5 years of age suffered from stunting and Indonesia is on the 5th place of country that suffers most from stunting.The main cause of stunting is unbalanced nutritional factors in quantity and quantity during growth period. Other causes are human factors (infant and child feeding practices, severe infections that cause wasting, subclinical infections, low birth weight babies and premature infants and social factors (household poverty, neglect of caregiving, unresponsive eating practices, inadequate child stimulation, food insecurity, limited health services, access to clean water and sanitation) Children can be predicted to be stunting by measuring height periodically since birth and most effective intervention to prevent stunting is to increase children‟s diet quality.The government role as program and policy makers is to create a Kerangka Intervensi Stunting (Stunting Intervention Framework), namely Specific Nutrition Interventions and Sensitive Nutrition Interventions.In conclusion, stunting can be predicted and can be prevented. Provision of MPASI in accordance with WHO recommendations that are timely, adequate, safe and are given in right manner is a specific nutrition intervention that can prevent stuntingKeywords: